Immunohistochemical evaluation for integrin binding sialoprotein on healing process of intrabony defect treated by bone sialoprotein - Jaafar , Mayada K.; Kadhim , Enas F (Journal of Baghdad College of Dentistry, 2022)
Background: Bone defect healing is a multidimensional procedure with an overlapping timeline that involves the regeneration of bone tissue. Due to bone’s ability to regenerate, the vast majority of bone abnormalities can be restored intuitively under the right physiological conditions. The goal of this study is to examine the immunohistochemistry of bone sialoprotein in order to determine the effect of local application of bone sialoprotein on the healing of a rat tibia generated bone defect. Materials and Methods: In this experiment, 48 albino male rats weighing 300-400 grams and aged 6-8 months will be employed under controlled temperature, drinking, and food consumption settings. The animals will be subjected to a surgical procedure on the medial side of the tibiae bone, with the bone defect repaired with absorbable hemostatic material in the control group (12 rats). The experimental group (12 rats) will be treated with local administration of 30 μl bone sialoprotein fixed by absorbable hemostatic sponge. After surgery, the rats will be slaughtered at 7, 14, and 28 days (four rats for each period). Results: Immunohistochemical analysis of bone sialoprotein by stromal cells reveal a substantial difference between the bone sialoprotein group and the control group. Conclusion: The study concludes that local application of bone sialoprotein could be a successful therapeutic treatment for bone injuries; these findings are encouraging for future clinical use.